The churches of God a treatise for the times : upon the constitution, government, discipline and ministyr of the Church of God and the principles and practice of service in the Gospel - Lang, George Henry, 1874-1958 (London, UK Paternaster, 1959)
Includes bibliographical references and index.
Brethren writer. Donated by Miss B. Jack, student 1959-60.
Keywords: Church